Selective Benzene Recognition in Competitive Solvent System (Cyclohexene, Cyclohexane, Tri- and Hexafluorobenzenes) Using Perfluorinated Dinuclear Cu(II) Complex - Kazuki Shiomoto; Nanako Oimatsu; Satoshi Hirano; Akiko Hori (Crystals)
The selective adsorption and separation of benzene from structurally similar six-membered hydrocarbons and fluorocarbons remain a significant challenge due to their comparable physical properties. In this study, we investigated the molecular recognition and separation properties of a perfluorinated triketonate Cu(II) complex (1) as a Nonporous Adaptive Crystal (NAC). In addition to the previously reported benzene (2)-encapsulated crystal of 1•(2)3, we report here the crystal structures of guest-free 1 and cyclohexene (3)-encapsulated 1•(O)2•3, where (O)2 represents two water molecules. Single-crystal analysis demonstrated that 1 selectively encapsulates 2 while excluding other hydrocarbons, including 3, cyclohexane (4), trifluorobenzene (5), and hexafluorobenzene (6). Gas adsorption experiments confirmed this high affinity for 2, as reflected in its preferential adsorption behavior in mixed solvent and vapor environments. The molecular selectivity of 1 was attributed to strong π-hole···π and metal···π interactions, which favor electron-rich aromatic guests. Additionally, crystallization experiments in competitive solvent systems consistently led to the formation of 1•(2)3, reinforcing the high selectivity of 1 for 2. These findings highlight the unique molecular recognition capabilities of NACs, providing valuable insights into the rational design of advanced molecular separation materials for industrial applications involving aromatic hydrocarbons. Hirshfeld surface analysis revealed that the contribution of F···F interactions to crystal packing decreased upon guest recognition (48.8% in 1, 34.2% in 1•(O)2•3, and 22.2% in 1•(2)3), while the contribution of F···H/H···F interactions increased (8.6% in 1, 22.2% in 1•(O)2•3, and 35.4% in 1•(2)3). Regarding Cu interactions, the self-assembled columnar structure of 1 results in close contacts at the coordination sites, including Cu···Cu (0.1%), Cu···O (0.7%), and Cu···C (1.3%). However, in the guest-incorporated structures 1•(O)2•3 and 1•(2)3, the Cu···Cu contribution disappears; instead, 1•(O)2•3 exhibits a significant increase in Cu···O interactions (1.2%), corresponding to water coordination, while 1•(2)3 shows an increase in Cu···C interactions (1.5%), indicative of the metal···π interactions of benzene.